2014
DOI: 10.1007/s40519-014-0164-x
|View full text |Cite
|
Sign up to set email alerts
|

Firm maternal parenting associated with decreased risk of excessive snacking in overweight children

Abstract: Objective To examine the relationship between parent feeding practices (restriction, monitoring, pressure to eat), general parenting behaviors (acceptance, psychological control, firm control), and aberrant child eating behaviors (emotional eating and excessive snacking) among overweight and normal weight children. Methods Overweight and normal weight children between 8 and 12 years old and their mothers (n=79 parent-child dyads) participated in this study. Mothers completed surveys on parent feeding practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
(86 reference statements)
0
11
1
Order By: Relevance
“…This is in contrast to several prior studies noting its maladaptive correlates (Faith et al, 2004; Fisher & Birch, 1999; Rhee et al, 2015; Rodgers et al, 2013). Restriction did , however, predict child SSB intake when authoritarianism was included in the model as a moderator.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to several prior studies noting its maladaptive correlates (Faith et al, 2004; Fisher & Birch, 1999; Rhee et al, 2015; Rodgers et al, 2013). Restriction did , however, predict child SSB intake when authoritarianism was included in the model as a moderator.…”
Section: Discussioncontrasting
confidence: 99%
“…Feeding practices are defined as “specific techniques or behaviors usually used to facilitate or limit ingestion of foods” (Blissett, 2011). Much attention has been given to two such practices, restriction and pressure to eat, both of which have been found to be counterproductive (Blissett, 2011; Rhee et al, 2015; Rodgers et al, 2013; Vereecken, Legiest, De Bourdeaudhuij, & Maes, 2009; Wardle, Carnell, & Cooke, 2005). For example, experimental research has demonstrated that restricting access to palatable foods results in children’s increased interest in and intake of such food (Fisher & Birch, 1999).…”
mentioning
confidence: 99%
“…Research is needed on parenting behaviors that shape child development through multiple mechanisms, including parent-child attachment relationships to develop trust, executive function skills (eg, paying attention, maintaining focus, planning), 69,70 and emotional regulation (eg, calming down when upset). 71 Parental behaviors also shape earlyemerging child health behaviors, including sleep habits, both duration and timing 72 ; engagement in physical and sedentary activity 73 ; media use 74,75 ; and eating behaviors 76,77 (eg, consumption of fruits and vegetables or sugar-sweetened beverages). 78,79 Little is known about the impact of sleep and sleep disorders on central cardiovascular control.…”
Section: Parenting Interventionsmentioning
confidence: 99%
“…On the social and cultural level, factors such as modeling behaviors from the family and social norms are related to snacking behavior. Rhee et al (18), for example, found that restrictive feeding practices by parents were related to decreased snack consumption among children (18), whereas Robinson et al (19) observed that messages that emphasize that the social norm is to limit junk food significantly reduced the intake of high-calorie snacks (19). In addition, organizational factors and the physical environment also affect snacking behaviors (13).…”
Section: Determinants Of Snackingmentioning
confidence: 99%